Civil Society, Power, and Public Accountability - Nandan J.C. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Democratic accountability is often understood as a function of constitutional design and institutional checks. While these mechanisms remain essential, political experience suggests that formal institutions alone are insufficient to restrain power or ensure responsible governance. Here we see that public accountability is sustained not merely through legal and administrative arrangements, but through the continuous engagement of civil society as a democratic space of vigilance, critique, and moral evaluation. Here the paper conceptualizes civil society as a sphere situated between state authority and private life, where citizens collectively monitor, question, and respond to the exercise of power. Drawing on classical and modern political thought, it examines how civic associations, social movements, media, and citizen networks contribute to democratic accountability by subjecting authority to public scrutiny. This analysis further considers how digital governance has transformed traditional modes of accountability, expanding opportunities for participation while simultaneously introducing new challenges such as fragmentation, misinformation, and performative activism. The central argument advanced is that accountability cannot be secured through institutions alone. It requires an active civic sphere capable of translating public concern into sustained political pressure. By foregrounding the relationship between civil society, power and accountability, the paper contributes to contemporary debates on democratic governance and highlights the enduring relevance of civic engagement in preserving democratic legitimacy.